Mifepristone for Treatment of Metabolic Syndrome: Beyond Cushing’s Syndrome - Francisco Díaz-Castro; Matías Monsalves-Álvarez; Matías Monsalves-Álvarez; Leonel E. Rojo; Leonel E. Rojo; Andrea del Campo; Rodrigo Troncoso; Rodrigo Troncoso (Frontiers in Pharmacology, 2020)
A growing body of research indicates that cortisol, the glucocorticoid product of the activation of the hypothalamic-pituitary-adrenal axis, plays a role in the pathophysiology of metabolic syndrome. In this regard, chronic exposure to cortisol is associated with risk factors related to metabolic syndrome like weight gain, type 2 diabetes, hypertension, among others. Mifepristone is the only FDA-approved drug with antiglucocorticoids properties for improved the glycemic control in patients with type 2 patients secondary to endogenous Cushing’s syndrome. Mifepristone also have been shown positive effects in rodents models of diabetes and patients with obesity due to antipsychotic treatment. However, the underlying molecular mechanisms are not fully understood. In this perspective, we summarized the literature regarding the beneficial effects of mifepristone in metabolic syndrome from animal studies to clinical research. Also, we propose a potential mechanism for the beneficial effects in insulin sensitivity which involved the regulation of mitochondrial function in muscle cells.